Efektivitas Media Pembelajaran Kotak Kartu Misterius (KoKaMi) untuk Meningkatkan Hasil Belajar Siswa pada Pelajaran Muthola’ah - Aufa Alfian Musthofa; Fera Favirotus Siyam; Alif Cahya Setiyadi; Yusvita Kusuma Wardani; Siti Aisyah (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2024)
In the era of globalization, mastering Arabic has become increasingly important as an international language used in many religious, academic, and professional contexts. Therefore, innovation in Arabic teaching methods is necessary to improve students' learning outcomes and motivate them to learn the language more effectively. This study aims to improve the learning outcomes of second-grade students at KMI Pondok Modern Al-Barokah Nganjuk in Muthola'ah lessons. By utilizing the Mysterious Card Box (KoKaMi) as a learning medium, this study focuses on implementing interactive and enjoyable teaching methods for the students. This research follows Kurt Lewin's Classroom Action Method, which consists of four stages: planning, acting, observing, and reflecting. The study was conducted in two cycles to determine the effectiveness of the KoKaMi learning medium and the students' learning outcomes. The subjects of this research are the second-grade students at KMI Pondok Modern Al-Barokah Nganjuk, totaling 16 students. The results of this study showed that the KoKaMi learning medium can be used by teachers to deliver Muthola'ah lessons while involving the students significantly. In the first cycle, 5 students passed with a percentage of 31.35%. In the second cycle, the number of students who passed increased to 11 students with a percentage of 93.75%. Based on the actions carried out over two cycles, it can be concluded that the KoKaMi learning medium is effective in delivering Muthola'ah lessons Class 2 students at KMI Pondok Modern Al-Barokah Nganjuk. Finally, the researcher hopes that in the future, this research can be used and be effective in research, especially research related to the Arabic language.